The use of laser capture microdissection to identify specific pathways and mechanisms involved in impulsive choice in rats. Issue 8 (August 2019) - Meda, Shirisha; Freund, Nadja; Norman, Kevin J.; Thompson, Britta S.; Sonntag, Kai-C.; Andersen, Susan L.
Abstract: Background: Microinjections, lesions, viral-mediated gene transfer, or designer receptors exclusively activated by designer drugs (DREADDs) can identify brain signaling pathways and their pharmacology in research animals. Genetically modified animals are used for more precise assessment of neural circuits. However, only a few of the gene-based pathway modifications are available for use in outbred rat strains. New method: Behaviorally characterized Sprague-Dawley rats undergo tract tracing through microinjection of fluorospheres, followed by laser capture microdissection (LCM) and qPCR for detecting mRNA of pathway-associated gene products. Correlations between mRNA expression and behavior identify specific involvement of pharmacologically relevant molecules within cells of interest. Here, we examined this methodology in an impulsive choice paradigm and targeted projections from the orbital and medial prefrontal cortex. Results: In this proof of concept study, we demonstrate relationships between measures of impulsive choice with distinct neurotransmitter receptor expression in cell populations from four different signaling pathways. Comparisons with existing methods: Combining behavior, tract tracing, LCM, and gene expression profiling provides more cellular selectivity than localized lesions and DREADDs, and greater pharmacological specificity than microinjections and viral-mediated gene transfer due to targeting identified neurons. Furthermore, the assessment of inter-individual pathways provides insight into the complex nature of underlying mechanisms involved in typical and atypical behavior. Conclusions: The novel combination of behavior, tract tracing, LCM, and single gene or potential whole genome transcriptome analysis allows for a more targeted understanding of the interconnection of neural circuitry with behavior, and holds promise to identify more specific drug targets that are relevant to behavioral phenotypes.